(untitled) (European Journal of Teaching and Education, 2020)
The current curriculum cannot meet the needs of students for learning and employment. In this study, the researchers shall improve students’ satisfaction with school-enterprise cooperation specialty by optimizing the curriculum of school-enterprise cooperation specialty. The article through the survey questionnaire and the literature research method was carried on the analysis and the discussion for this study. This provides an important development direction for the school-enterprise cooperation professional curriculum development. One the one hand, students can master more practical skills. It can also improve the satisfaction and success rate both school and enterprise, and promote long-term and stable cooperative relationship. To achieve a win-win situation for schools, enterprises and students.